MSME Business Performance: Affecting Factors of Networking, Work Culture and Reputation - Abidin, Zainal; Majid, Jamaluddin; Hamid, Nurasiah (Jurnal Minds: Manajemen Ide dan Inspirasi, 2023)
Micro, Small and Medium Enterprises (MSMEs) are crucial in increasing Indonesia's GDP, as indicated by the number of MSMEs in Indonesia, estimated at around 50 million businesses. This study assesses the importance of networking, work culture, and reputation in developing MSMEs so that MSMEs can absorb a broad local workforce. The total population is 260 MSME actors in South Sulawesi. The data is then regressed using SmartPLS to get the findings. The results of the study show that networking and work culture has a positive and significant effect on business performance and reputation. Reputation has a positive but not significant impact on business performance. Indirectly, network and work culture positively but not significantly affect business performance through reputation.